The Tradition of Visiting the Tomb of Rade Naru and the Socio-Religious Dynamics of the Wora Village Community - Arhan Arhan; Kurniawan; Arfaton (Tabéq: Journal of Local Wisdom, Belief, and Peace, 2025)
Indonesia, as a multicultural nation, has deeply rooted religious traditions in its people’s lives, among them the practice of grave pilgrimage. In Wora Village, Bima, the tradition of visiting the grave of Rade Naru symbolizes respect for ancestors and serves as a spiritual and social means of strengthening community solidarity. However, this practice creates tension between local culture and normative Islamic teachings, as some religious leaders consider it potentially syirik (polytheism). At the same time, the indigenous community maintains it as a sacred ancestral heritage. This study employed qualitative methods with a sociological approach. This study employed Max Weber’s theory of social action to analyze the traditional motivations, values, and affective aspects of the community in undertaking the pilgrimage. The results show that the pilgrimage to the grave of Rade Naru functions not only as a religious ritual but also as an arena for contestation of authority between traditional and religious leaders, as well as an instrument for strengthening collective identity. Thus, this tradition reflects the resilience of local culture amidst modernization and normative Islamic preaching, while also providing a space for dialogue between religion, culture, and the community’s social identity.